KONSEPSI NEGARA HUKUM PANCASILA DAN IMPLEMENTASINYA DI INDONESIA - Tubagus Muhammad Nasarudin (PRANATA HUKUM, 2020)
The rule of law in the perspective of Pancasila which can be termed the law state of Indonesia or the rule of law state of Pancasila besides having the same elements as the rule of law in the rechtstaat and rule of law, also has specific elements that make the Indonesian law state different from the concept of the state generally known law. The difference locates in the values contained in the Preamble to the 1945 Constitution which contain Pancasila with the principles of the Belief in the one and only God and the absence of separation between the state and religion, the principle of deliberation in the implementation of state government power, the principle of social justice, kinship and mutual cooperation, as well as laws that serve the integrity of the unitary state of Indonesia. The Pancasila Law State concept is characterized by: (1) Close relations between religion and state (2) Stand on the one and only God (3) Freedom of religion in a positive sense (4) Atheism is not justified and communism is forbidden and (5) The principle of kinship and harmony. As for the main elements of the Republic of Indonesia Law State are: (1) Pancasila (2) MPR (3) Constitutional system (4) equality and (5) Free trial.